Benefits of Teacher Diversity: Leading for Transformative Change (Journal of School Administration Research and Development, 2019)
This essay articulates the benefits of teacher diversity by illustrating six themes: a) leading for social justice through local and global civic engagement; b) developing an inclusive school culture; c) culturally relevant pedagogy; d) cultural translators and transformers; e) role models; and (f) benefits accrued by White students. The authors draw from evidence in supporting arguments surrounding the benefits accrued when teacher diversity reflects the demographics of students served and the role educational leaders can play in advancing efforts to recruit and retain a diverse faculty pool. They challenge readers to consider the benefits accrued when deliberate efforts to increase teacher diversity are made in light of advancing student academic success.